Original Research: An Investigation of Career Choice Regret Among American Nurses. Issue 4 (April 2020) - Dyrbye, Liselotte; West, Colin; Johnson, Pamela; Cipriano, Pamela; Peterson, Cheryl; Beatty, Dale; Major-Elechi, Brittny; Shanafelt, Tait
ABSTRACT: Purpose: To explore whether burnout is an independent predictor of career choice regret among nurses. Methods: In November 2017 we invited a random sample of 89, 995 members of the American Nurses Association to participate in an anonymous online survey. The survey collected demographic and professional information and included the Maslach Burnout Inventory–Human Services Survey for Medical Personnel (known as the MBI-HSS [MP]), as well as several items exploring career choice regret. Of the 86, 858 nurses who received the e-mail invitation, 8, 638 (9.9%) responded. Multivariable logistic regression analysis was conducted for the final sample of 6, 933 nurses who provided complete responses to the MBI-HSS (MP) and the career choice regret survey items. Results: Fifteen percent of the 6, 933 participating nurses had career choice regret. On multivariable analysis, experiencing burnout, working unplanned or mandatory overtime, being male, and having a higher academic degree related to nursing were independent predictors of career choice regret. Burnout was the strongest such predictor. Conclusion: Career choice regret among U.S. nurses is relatively common. Of the independent predictors this study identified, burnout had the strongest relationship with career choice regret. Organizational strategies aimed at reducing burnout and supporting nurses' ongoing professional development should be pursued. Abstract : The authors surveyed a random sample of American Nurses Association members to find out the extent of career choice regret among U.S. nurses and whether burnout is an independent predictor.